Evaluation of immobilization and hydrolytic properties of α-amylase onto ‎chitosan-PVA copolymer - Atul; Kaur, Inderjeet; Sharma, Aarti (International Journal of Advanced Chemistry, 2025)
The immobilization of α-amylase onto the chitosan-PVA (Chs-co-PVA) copolymer was successfully achieved ‎through physical ad-sorption from its suspension in tris-HCl buffer (0.1 M, pH 8.0, with an activity of 2.89 U/mL). ‎The process resulted in a maximum protein binding efficiency of 79.28% at pH 8.0, with 20.72% of the enzyme ‎remaining unbound. The hydrolysis of starch by both free α-amylase and copolymer-bound α-amylase was ‎evaluated under various reaction conditions. It was found that the immobilized α-amylase exhibited enhanced ‎activity and stability compared to the free enzyme, particularly at elevated temperatures, extended incubation ‎times (50 minutes), and an optimal pH of 8.0. The presence of specific salt ions, including Mg²⁺, Co²⁺, Fe³⁺, Ca²⁺, K⁺, ‎Zn²⁺, Na⁺, Pb²⁺, Hg²⁺, and Cu²⁺, further improved the hydrolytic activity of the immobilized enzyme compared to the ‎free enzyme. Additionally, immobilized α-amylase also demonstrated greater thermo stability, reusability, and ‎storage stability‎.